2013
DOI: 10.1177/0957650912473543
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of moment coefficient and flow structure in a rotor–stator cavity with rotor-mounted bolts

Abstract: The torque associated with overcoming the losses on a rotating disc is of particular importance to the designers of gas turbine engines. Not only does this represent a reduction in useful work, but it also gives rise to unwanted heating of metal surfaces and the adjacent fluid. This article presents a numerical study on the effect of rotor-mounted bolts on the moment coefficient and velocity distributions within a rotor–stator cavity under conditions representative of modern gas turbine engine design. Steady-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Figure 17 shows a comparison between the measured values of moment coefficient of all six configurations and those predicted by Eq. (20). There is a good agreement, generally within 6%, between the measured and the correlated data.…”
Section: Correlation Of the New Data For Plain Diskmentioning
confidence: 78%
See 2 more Smart Citations
“…Figure 17 shows a comparison between the measured values of moment coefficient of all six configurations and those predicted by Eq. (20). There is a good agreement, generally within 6%, between the measured and the correlated data.…”
Section: Correlation Of the New Data For Plain Diskmentioning
confidence: 78%
“…Coren et al, (2007) [18] and Miles (2012) [19] carried out an experimental study on windage effects in rotor-stator cavities for both plain disk and the rotor with protruding bolts. Moghaddam et al (2013) [20] conducted a numerical study that showed that the moment coefficient increased significantly with an increasing, yet limited, number of bolts. Long et al (2012) [21] carried out experiments with hexagonal and bihexagonal rotor bolts and a single design of rotor pocket.…”
Section: Review Of Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Moghaddam et al. 20 investigated the effect of bolts on the rotor surface, on moment coefficient, and the flow structure, in a shrouded rotor–stator system with superimposed throughflow. The steady CFD simulations were carried out using periodic sector models varying the number of bolts in the range 0 ≤ n ≤ 60.…”
Section: Introductionmentioning
confidence: 99%
“…The CFD studies on disc cavities with bolts or protrusions have focused primarily on the validation of predicted disc torque by comparison with measured values, assuming that the flow is steady and periodic. Moghaddam et al 20 investigated the effect of bolts on the rotor surface, on moment coefficient, and the flow structure, in a shrouded rotor-stator system with superimposed throughflow. The steady CFD simulations were carried out using periodic sector models varying the number of bolts in the range 0 4 n 4 60.…”
Section: Introductionmentioning
confidence: 99%